Full-mouth disinfection as a therapeutic protocol for type-2 diabetic subjects with chronic periodontitis: Twelve-month clinical outcomes. A randomized controlled clinical trial - Santos, Vanessa R.; Lima, Jadson A.; Miranda, Tamires S.; Gonçalves, Tiago E. D.; Figueiredo, Luciene C.; Faveri, Marcelo; Duarte, Poliana M. (Journal of clinical periodontology, 2013)
Aim The aim of this randomized controlled clinical trial was to evaluate the clinical effects of chlorhexidine (CHX) application in a full‐mouth disinfection (FMD) protocol in poorly controlled type‐2 diabetic subjects with generalized chronic periodontitis. Material and Methods Thirty‐eight subjects were randomly assigned into FMD group (n=19): full‐mouth scaling and root planing (FMSRP) within 24 h + local application of CHX gel + CHX rinses for 60 days or Control group (n = 19): FMSRP within 24 h + local application of placebo gel + placebo rinses for 60 days. Clinical parameters, glycated haemoglobin and fasting plasma glucose were assessed at baseline, 3, 6 and 12 months post‐therapies. Results All clinical parameters improved significantly at 3, 6 and 12 months post‐therapies for both groups (p < 0.05). There were no significant differences between groups for any clinical parameters, and glycemic condition at any time‐point (p > 0.05). Conclusions The treatments did not differ with respect to clinical parameters, including the primary outcome variable (i.e. changes in clinical attachment level in deep pockets), for up to 12 months post‐treatments.